The Strange Ones: Exploring A Young Adult’s Behavior as She Goes Through Rejection and Acceptance of Her Self-Identity - Edlyn Gracia Soewarsono (Institute of Research and Community Outreach - Petra Christian University, 2018)
This creative work is about a young adult who is excited to explore her identity of someone who has a magical ability. It explores the issue of identities in young adults and its correlation to rebellion in the form of running away, which is common in Indonesia. It aims to bring the readers alongside the main character on her journey of exploring her identity, as well as dealing with her parents’ rejection of the identity that she is most comfortable in. To further understand how she deals with her parents’ pressure to take an identity she does not like, Erik Erikson’s fifth psychosocial stage—Identity vs. Role confusion is used as the first theory of this work. The second theory, James Marcia’s identity status, is used to understand how the main character explores her identity in different statuses. The genre of this creative work is low fantasy, which is a subgenre of fantasy that uses minimal magical elements and is set in the real world.